Efficacy of a Complex of 5-Aminolevulinic Acid and Glycyl-Histidyl-Lysine Peptide on Hair Growth - Lee, Weon Ju; Sim, Hyun Bo; Jang, Yong Hyun; Lee, Seok-Jong; Kim, Do Won; Yim, Soon-Ho (Annals of dermatology, 2016)
Pattern hair loss is a very common problem. Although effective therapeutics for the treatment of pattern hair loss have been used, novel therapeutic modalities are still required to enhance hair growth. We investigated the efficacy and safety of a complex (ALAVAX) of 5-aminolevulinic acid (5-ALA) and glycyl-histidyl-lysine (GHK) peptide for the treatment of pattern hair loss. Forty-five patients with male pattern hair loss were treated with ALAVAX 100 mg/ml (group A), ALAVAX 50 mg/ml (group B) or placebo (group C) once a day for 6 months. Total hair count, hair length, hair thickness, patient's assessment and adverse events were evaluated at month 1, 3, and 6. An increase in hair count for 6 months was 52.6 (p<0.05) in group A, 71.5 (p<0.05) in group B, and 9.6 in group C. The ratio of changes in hair count between group B (2.38) and group C (1.21) at 6 months showed a statistically significant difference (p<0.05). The proportion above good satisfaction was higher in group A (26.7%) than in the other groups (group B: 14.3%, group C: 7.1%). There was no statistically significant difference in hair length and hair thickness among 3 groups at 6 months. There was no adverse event in 3 groups. Our study showed that a complex of 5-ALA and GHK peptide may be considered as one of the complementary agents for the treatment of male pattern hair loss.